IMPROVING CHILDREN'S INTRAPERSONAL INTELLIGENCE THROUGH DRAGON GAMES - Kholifah, Eka Setiawati, Hadi Sutiawan (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
This research was conducted in early childhood in the background with many children who do not know the needs of themselves and others due to a lack of communication and socialization to children, families and their environment. Therefore, learning activities are needed that can increase intrapersonal intelligence in children from an early age because at an early age it is very good to apply learning that stimulates intrapersonal intelligence to make children a good person. This research method is the Classroom Action Research (PTK) method. The subject of the study was group A students at PAUD Al Falah Kubang Puji. The data collection techniques are observation, interviews, and documentation. The learning method using the dragon snake game carried out at PAUD Al-Falah Kubang Puji, aims to determine the development of children in increasing intrapersonal intelligence. The results of the study in the pre-cycle were 49.1%, increased in the first cycle by 67.1%, and in the second cycle increased by 80.8%. So the conclusion is that through the dragon snake game can increase intrapersonal intelligence in children.